Sustainable Development of Energy, Water and Environment Systems (SDEWES 2022) - Sahin, Oz; Richards, Russell (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Implementing sustainable development is central to achieving global reductions in greenhouse gas emissions and mitigating anthropogenic environmental impacts. As defined by the UN 2030 Agenda and its associated Sustainable Development Goals (SDGs), sustainable development requires a holistic, interdisciplinary approach, which is not without its challenges. Indeed, studies tracking global progress toward meeting the 2030 SDG targets emphasize the importance of implementing sustainable solutions, with several SDG targets described as 'off track.' Therefore, there is an urgent need to address the challenges of an interdisciplinary, unified, and practical approach to sustainable implementation. In this context, this Reprint brings together 15 selected papers presented during the 2022 SDEWES Conference. These papers cover a broad range of topics, from circular governance models to education related to sustainable practices, as well as the impacts of current legislative frameworks targeting energy efficiency, built environment energy performance, bio-based industrial applications, transport and sustainable energy services, and production, supply, and infrastructure maintenance strategies. This Reprint provides an interdisciplinary and holistic perspective on sustainable development solutions, with several papers highlighting the interrelations between various fields and aspects of sustainability.